2020
DOI: 10.1108/ijem-04-2019-0146
|View full text |Cite
|
Sign up to set email alerts
|

Leadership style and teacher performance: mediating role of occupational perception

Abstract: Purpose The purpose of this paper is to develop a model in which leadership styles (transformational or transactional leadership) directly and indirectly (through occupation perception) affect teacher performance (in-role performance and organizational citizenship behavior (OCB)). Design/methodology/approach The research hypothesis holds that the leadership style (transformational or transactional) has a direct and indirect effect on teacher performance (through occupation perception). These hypotheses have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 72 publications
(123 reference statements)
4
33
0
1
Order By: Relevance
“…The findings of this study are supported by previous research conducted by Alzoraiki et al (2018) shows that all the dimensions of transformational leadership have a positive influence on the teachers' performance. It is also in line with a study conducted by Nasra & Arar (2019) that teachers' performance increases as they perceive their principals' leadership style as more transformational and less transactional. This is also supported by other research conducted by (Anwar, 2018) entitled "The Influence of Principal's Transformational Leadership on Teacher Performance at SMPN 1 Awangpone, Bone Regency", stating that there is an effect of the principal's transformational leadership on teacher performance.…”
Section: There Is a Contribution Of Transformational Leadership To Teacher Performancesupporting
confidence: 89%
“…The findings of this study are supported by previous research conducted by Alzoraiki et al (2018) shows that all the dimensions of transformational leadership have a positive influence on the teachers' performance. It is also in line with a study conducted by Nasra & Arar (2019) that teachers' performance increases as they perceive their principals' leadership style as more transformational and less transactional. This is also supported by other research conducted by (Anwar, 2018) entitled "The Influence of Principal's Transformational Leadership on Teacher Performance at SMPN 1 Awangpone, Bone Regency", stating that there is an effect of the principal's transformational leadership on teacher performance.…”
Section: There Is a Contribution Of Transformational Leadership To Teacher Performancesupporting
confidence: 89%
“…al, 2020;Ahmadiansah, 2016), while the result of research conducted by Noermijati (2015) showed a negative impact. The research conducted by Nasra (2019) showed that transformational leadership has a positive significant effect towards the performance. In the other hand, research conducted by Shahab & Nisa (2014) showed that transformational leadership has negative significant effect towards the performance.…”
Section: Introductionmentioning
confidence: 99%
“…The teacher is unable to show his competence as a professional in the field of teaching. Nasra et al (2019), to improve the performance of teachers in schools the role of the principal's leadership is needed, especially to increase teacher competence in their teaching duties.…”
Section: Discussionmentioning
confidence: 99%